2021
DOI: 10.18632/aging.203215
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell-free circRNAs panel act as fingerprint predicts the occurrence of laryngeal squamous cell carcinoma

Abstract: Background: Circular RNAs (circRNAs) have recently emerged as a new class of RNAs, highly enriched in the human tissues and very stable within cells, exosomes and body uids. In this study, we aimed to screen the plasma cell-free derived circRNAs in laryngeal squamous cell carcinoma (LSCC) and investigate whether these circRNAs could predicted LSCC as potential biomarkers.Methods: The circRNA microarray was employed with three samples in each group to screen the dysregulated circRNAs isolated from plasma sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…It demonstrates an AUC of 0.805, with a sensitivity of 0.823 and a specificity of 0.694 127 . Furthermore, circ0019201, circ0011773, and circ0122790 upregulated in the plasma of patients with LSCC, with AUC of 0.766, 0.864, and 0.908, respectively, suggesting their potential as predictive biomarkers for LSCC 128 . Moreover, circMORC3 downregulation in HSCC tissues and plasma, with an AUC of 0.767, suggests its potential as an early diagnostic biomarker for HNSCC 129 (Table 1 ).…”
Section: Potential Of Circrna As Diagnostic and Prognostic Biomarkers...mentioning
confidence: 99%
“…It demonstrates an AUC of 0.805, with a sensitivity of 0.823 and a specificity of 0.694 127 . Furthermore, circ0019201, circ0011773, and circ0122790 upregulated in the plasma of patients with LSCC, with AUC of 0.766, 0.864, and 0.908, respectively, suggesting their potential as predictive biomarkers for LSCC 128 . Moreover, circMORC3 downregulation in HSCC tissues and plasma, with an AUC of 0.767, suggests its potential as an early diagnostic biomarker for HNSCC 129 (Table 1 ).…”
Section: Potential Of Circrna As Diagnostic and Prognostic Biomarkers...mentioning
confidence: 99%
“…Likewise, high exosomal circMYC expression in the multiple myeloma patients' serums implied that the patients might have higher relapse rates and higher mortality rates [116]. In laryngeal squamous cell carcinoma, three serum exosomal circRNAs consisted of circ_0019201, circ_0011773 and circ_0122790 could be used as an early prediction model for occurrence of tumor [112]. II) Poor prognosis prediction: Through the detection of serum exosomes, the abnormal expression of some tumor-driven exosomal circRNAs also indicated the poor prognosis of cancer patients.…”
Section: Tumor-driven Exosomal Circrnas and Diagnosismentioning
confidence: 99%
“…Han et al [ 62 ] showed that plasma circ_0019201, circ_0011773, and circ_0122790 are potential biomarkers for predicting LSCC. Circ_0019201, circ_0011773, and circ_0122790 were found to be consistent with the training set.…”
Section: Role Of Exosomal Circrnas In Diagnosis and Prognosismentioning
confidence: 99%